Adenoviral-Vectored Mayaro and Chikungunya Virus Vaccine Candidates Afford Partial Cross-Protection From Lethal Challenge in A129 Mouse Model - Campos, Rafael Kroon; Preciado-Llanes, Lorena; Azar, Sasha R.; Kim, Young Chan; Brandon, Olivia; López-Camacho, César; Reyes-Sandoval, Arturo; Rossi, Shannan L. (Frontiers in Immunology, 2020)
Mayaro (MAYV) and chikungunya viruses (CHIKV) are vector-borne arthritogenic alphaviruses that cause acute febrile illnesses. CHIKV is widespread and has recently caused large urban outbreaks, whereas the distribution of MAYV is restricted to tropical areas in South America with small and sporadic outbreaks. Because MAYV and CHIKV are closely related and have high amino acid similarity, we investigated whether vaccination against one could provide cross-protection against the other. We vaccinated A129 mice (IFNAR −/−) with vaccines based on chimpanzee adenoviral vectors encoding the structural proteins of either MAYV or CHIKV. ChAdOx1 May is a novel vaccine against MAYV, whereas ChAdOx1 Chik is a vaccine against CHIKV already undergoing early phase I clinical trials. We demonstrate that ChAdOx1 May was able to afford full protection against MAYV challenge in mice, with most samples yielding neutralizing PRNT80 antibody titers of 1:258. ChAdOx1 May also provided partial cross-protection against CHIKV, with protection being assessed using the following parameters: survival, weight loss, foot swelling and viremia. Reciprocally, ChAdOx1 Chik vaccination reduced MAYV viral load, as well as morbidity and lethality caused by this virus, but did not protect against foot swelling. The cross-protection observed is likely to be, at least in part, secondary to cross-neutralizing antibodies induced by both vaccines. In summary, our findings suggest that ChAdOx1 Chik and ChAdOx1 May vaccines are not only efficacious against CHIKV and MAYV, respectively, but also afford partial heterologous cross-protection.